Experimental models of non-alcoholic fatty liver disease in rats - Kucera, Otto (Baishideng Publishing Group Inc, 2014)
Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in the Western world, and it persists at a high prevalence. NAFLD is characterised by the accumulation of triglycerides in the liver and includes a spectrum of histopathological findings, ranging from simple fatty liver through non-alcoholic steatohepatitis (NASH) to fibrosis and ultimately cirrhosis, which may progress to hepatocellular carcinoma. The pathogenesis of NAFLD is closely related to the metabolic syndrome and insulin resistance. Understanding the pathophysiology and treatment of NAFLD in humans has currently been limited by the lack of satisfactory animal models. The ideal animal model for NAFLD should reflect all aspects of the intricate etiopathogenesis of human NAFLD and the typical histological findings of its different stages. Within the past several years, great emphasis has been placed on the development of an appropriate model for human NASH. This paper reviews the widely used experimental models of NAFLD in rats. We discuss nutritional, genetic and combined models of NAFLD and their pros and cons. The choice of a suitable animal model for this disease while respecting its limitations may help to improve the understanding of its complex pathogenesis and to discover appropriate therapeutic strategies. Considering the legislative, ethical, economical and health factors of NAFLD, animal models are essential tools for the research of this disease.